Impact of Work-Function Variation in Ferroelectric Field-Effect Transistor - Yeon Jung, Su; Kim, Hyunwoo; Lee, Jongmin; Hyun Kim, Jang (IEEE Journal of the Electron Devices Society, 2024)
We analyzed the impact of work-function variation (WFV) in ferroelectric field-effect transistor (FeFET). To analyze the operation characteristics, we employed the technology computer-aided design (TCAD) simulations. After evaluating ferroelectricity (FE) characteristics and optimizing device model parameters through calibration, we extracted five key parameters from the hysteretic transfer curves of the FeFET: threshold voltage (Vth), on current (Iin), subthreshold swing (SS), off current (Ioff), and gate-induced drain leakage (GIDL). The extracted parameters were compared based on the presence or absence of FE and the ferroelectric thickness. It was confirmed that the presence of FE leads to increased variation due to dipole alignment with WFV, and that the electric field is maintained even with an increase in ferroelectric thickness
Keywords: Design simulations; Dipole alignment; Ferroelectric field-effect transistor; Ferroelectric fieldeffect transistors (FeFET); Ferroelectric thickness; Ferroelectricity; Function variation; Operation characteristic; Technology computer aided design; Work-function variation; dipole alignment; electric field; ferroelectric; Ferroelectric field-effect transistor (FeFET); ferroelectricity (FE); work-function variation (WFV)